Admission Serum Uric Acid Levels and In-Hospital Outcomes in Patients with Acute Coronary Syndrome (Journal of Enam Medical College, 2015)
Background: Uric acid is an independent risk factor for cardiovascular disease. Hospital admission for ischemic heart disease (IHD) is increasing rapidly in our country. Although studies were conducted abroad regarding association of serum uric acid with in-hospital outcomes in patients with acute coronary syndrome (ACS), no data is yet available to show the association in our country. Objective: The objective of this study was to assess the association of serum uric acid level on admission with in-hospital outcomes of the patients with ACS. Materials and Methods: This cross sectional comparative study was done in the Department of Cardiology, Dhaka Medical College Hospital (DMCH) from January to December 2012. After proper ethical consideration total 93 ACS patients were enrolled in the study by nonrandom sampling. Serum uric acid of all subjects was measured within 24 hours of admission. Then in-hospital outcomes were observed in all subjects. Results: The frequency of hyperuricemia among ACS patients was 24.7% (22.54% in male and 31.82% in female). Hyperuricemic patients significantly developed heart failure (30.4% vs 11.4%, p=0.032) and conduction defect (13.0% vs 1.4%, p=0.017) than normouricemic subjects. The mean ejection fraction was significantly lower in hyperuricemic patients than patients with normal uric acid level (50.87 ± 10.27% vs 55.94 ± 6.66%). The mean ± SD duration of hospital stay of hyperuricemic group was significantly longer in patients with ACS (8.26 ± 1.18 vs 7.51±1.18 days, p=0.010). Conclusion: The measurement of serum uric acid level, an easily available and inexpensive biochemical tool, might turn out as a valuable risk marker for prediction of in-hospital outcomes in patients with ACS. DOI: http://dx.doi.org/10.3329/jemc.v5i1.21492 J Enam Med Col 2015; 5(1): 15-22